Access to legal records by children leaving State care: The experience of young people in NSW. (March 2019) - Greenwood, Brooke; Mansour, Julia; Winnett, Celia
For those who have been in the care of the State as children, access to records can be critical to securing justice and redress for past wrongs. This article outlines the arguments made in recent litigation undertaken by the Public Interest Advocacy Centre (PIAC) on behalf of young people who requested access to legal audits conducted on their files by the New South Wales (NSW) Department of Family and Community Services (FACS). It documents the policy change that was achieved as a result of the litigation and makes recommendations for further reform to better realise the rights of children in care to access their records.